Effects of SARS-COV-2 infection on outcomes in patients hospitalized for acute cardiac conditions. A prospective, multicenter cohort study (Swiss Cardiovascular SARS-CoV-2 Consortium) - Koskinas, Konstantinos C.; Twerenbold, Raphael; Carballo, David; Matter, Christian M.; Cook, Stephane; Heg, Dik; Frenk, Andre; Windecker, Stephan; Osswald, Stefan; Lüscher, Thomas F.; Mach, Francois (Frontiers in Cardiovascular Medicine, 2023)
Background Although the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) causing coronavirus disease 2019 (COVID-19) primarily affects the respiratory system, the disease entity has been associated with cardiovascular complications. This study sought to assess the effect of concomitant SARS-COV-2 infection on clinical outcomes of patients hospitalized primarily for acute cardiac conditions on cardiology wards in Switzerland. Methods In this prospective, observational study conducted in 5 Swiss cardiology centers during the COVID-19 pandemic, patients hospitalized due to acute cardiac conditions underwent a reverse-transcriptase polymerase chain reaction test at the time of admission and were categorized as SARS-COV-2 positive (cases) or negative (controls). Patients hospitalized on cardiology wards underwent treatment for the principal acute cardiac condition according to local practice. Clinical outcomes were recorded in-hospital, at 30 days, and after 1 year and compared between cases and controls. To adjust for imbalanced baseline characteristics, a subgroup of patients derived by propensity matching was analyzed. Results Between March 2020 and February 2022, 538 patients were enrolled including 122 cases and 416 controls. Mean age was 68.0 ± 14.7 years, and 75% were men. Compared with controls, SARS-COV-2-positive patients more commonly presented with acute heart failure (35% vs. 17%) or major arrhythmia (31% vs. 9%), but less commonly with acute coronary syndrome (26% vs. 53%) or severe aortic stenosis (4% vs. 18%). Mortality was significantly higher in cases vs. controls in-hospital (16% vs. 1%), at 30 days (19.0% vs. 2.2%), and at 1 year (28.7% vs. 7.6%: p < 0.001 for all); this was driven primarily (up to 30 days) and exclusively (at one-year follow-up) by higher non-cardiovascular mortality, and was accompanied by a greater incidence of worsening renal function in cases vs. controls. These findings were maintained in a propensity-matched subgroup of 186 patients (93 cases and 93 controls) with balanced clinical presentation and baseline characteristics. Conclusions In this observational study of patients hospitalized for acute cardiac conditions, SARS-COV-2 infection at index hospitalization was associated with markedly higher all-cause and non-cardiovascular mortality throughout one-year follow-up. These findings highlight the need for effective, multifaceted management of both cardiac and non-cardiac morbidities and prolonged surveillance in patients with acute cardiac conditions complicated by SARS-COV-2 infection.